Tristram Shandy, Philosopher. Issue 2 (23rd February 2017) - Hawley, Judith
ABSTRACT: Sterne's narrator is concerned about his status and role in life. On the title page of his Life and Opinions, he designates himself a 'Gentleman'. What kind of writer he is, and how his Life and Opinions should be shelved in the library, has been the subject of debate. Chiefly, critics have discussed whether Tristram Shandy is more appropriately classed as a satire or a novel. Whether or not Sterne thought of himself as writing a novel, Tristram did not. He is writing his Life and it is a life of the mind rather than of adventures. 'I write, ' Tristram declares, 'as a man of erudition'. He also writes as a philosopher. He refers to his life and opinions as a book 'of strict morality and close reasoning'. Critics and philosophers have understandably taken seriously Sterne's treatment of philosophy and have read Tristram Shandy in the light of the philosophers of the long eighteenth century, especially Locke and Hume. This essay will suggest that Tristram's sense of his shelf-mates in both philosophy and literature does not fit modern academic categories. It will consider what Tristram meant and his readers might have understood by the term 'philosophy' and argue that while Tristram Shandy might be a philosophical novel, it does not constitute philosophy.